Multiple watermarking for copyright protection using DWT and dual-tree CWT. (1st January 2011) - Kamble, Sushila; Maheshkar, Vikas; Agarwal, Suneeta; Srivastava, Vinay Kumar
This paper proposes two techniques for multiple image watermarking based on discrete wavelet transform (DWT) and dual-tree complex wavelet transform (DT-CWT) using spread transform. The proposed scheme embed two watermarks by spreading the orthogonal projection vectors into the cover vectors extracted from the first level decomposition discrete wavelet coefficients in first technique and dual tree CWT coefficients of the host image in the second technique. The spread transform disperse the watermark over a large number of frequencies providing robustness to geometric attacks like rotation, scaling, cropping, etc., as well as compression like JPEG. The multiple watermark signals are embedded in different orientations of projection vectors which increase the embedding capacity as compared to the single watermark embedding techniques. The experimental results show that the watermarked image by both the techniques has good visual quality in terms of PSNR. Thus the proposed scheme provides the balanced trade off between important parameters of watermarking, i.e., capacity, robustness and imperceptibility.